The Feasibility Study of the Adaptation of the Crime of Baghy (Arabic: اَلْبَغْي, lit: trespass or insolence) to Soft Power in Islamic Jurisprudence - Arash Gharibi; Ruhollah Akrami (مطالعات فقه اسلامی و مبانی حقوق, 2024)
Baghy (Arabic: اَلْبَغْي, lit: trespass or insolence) according to Islamic jurists is called a group armed actions against the Islamic government. Although the title of “baghy” is new in the Islamic Penal Code, its discussion is well known in jurisprudence. The rulings related to “baghy” have long been discussed in jurisprudential books and within the discussions of jihād (Arabic: جِهَاد). However, there is another type of threat against the Islamic government, which is called soft power. Now, the important question that comes to mind is that will those who commit soft threats against the basis of the Islamic system be subject to the title of “baghy”? It seems by an analytical-descriptive method in the form of studying and searching the verses, aḥādīth (traditions), and the views of contemporary and recent jurists, and what is obtained from reliable sources and fatāwā (legal rulings on a point of Islamic law) of Islamic jurists, that the compatibility of the two mentioned titles with regard to the jurisprudential conditions mentioned in the discussions related to “baghy” can be imagined in cases in which in some forms of soft power, the perpetrators are considered to be subject to the crime of “baghy” and enforced upon them the rulings of the rebels (Arabic: بُغَات, bughāt).